Motocyclistic accidents in São Bernardo do Campo, SP, between 2003 and 2005 - Tognini, Silvana (2008)
The objective of this study is to analyze by epidemiological optic, the occurrence of motorcyclist accidents in São Bernardo do Campo (SP) during the period between 2003 and 2005. Initial methodology was the bibliographical survey, as a basis for the field research carried out in a transversal study in which the data had been proceeding from the Comunicações de Acidentes de Trabalho(Workers Accidents Report Form) (CAT's) referring to the accidents with motorcyclists in the period from 2003 to 2005 in the city of São Bernardo do Campo. The following information had been collected: age, sex, accident’s schedule, period of the week, year, type of accident, region of occurrence and anatomical localization of the injury. To verify the association between type, place, hour and day of accident, the qui- square test was used. The level of significance was (5%). It was concluded through this study that São Bernardo do Campo City pertaining to the ABRAMET’s citations, with exception of the increased rate of the accidents in the age group of the 40-49 years in 2005, that can be justified by the tax of unemployment in São Paulo Metropolitan Region, where working with motorcycles in different tasks becomes viable for survival and familiar help. Considering the analysis of 444 CAT's from the 2003 to 2005’s in São Bernardo do Campo, it was possible to verify that the number of accidents with motorcycles is increased, in comparison with the tax of accidents in the State of São Paulo.